Pengembangan Media Jenga Aksara Jawa dalam Pembelajaran Membaca dan Menulis Teks Berhuruf Jawa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Abstract There was no development of Javanese script learning media impacted with the less interesting and ineffective learning process so that students have difficulty in understanding Javanese script material. This study aimed to describe the students and teachers’ needs for Javanese script learning media, describe the prototype of the Javanese script Jenga media, and describe the results of the validation of media and material experts on the Javanese script Jenga media. The method of this study used Research and Development. Then, in collecting data this study used interview and questionnaire techniques. The data collected were analyzed using descriptive qualitative and quantitative descriptive analysis techniques. Based on the results of this study, it can be seen that students and teachers need an interesting and effective learning media to help them easier in understanding Javanese script material. The prototype of the Javanese Script Jenga media consists of a media box, Javanese Script Jenga wooden block, cards and their boxs, dice, blackboard, markers, students’ guidebook, and teacher's manual handout with practice questions and answer keys. Based on the assessment result, Jenga Aksara Jawa media prototype obtained an assessment percentage of 80% from media experts and 77.6% from material experts. Expert validators also provided suggestions and input that can be received into consideration by researchers to improve the Javanese script Jenga media prototype shortcomings. Therefore, this Javanese script media is proper to be used as a learning media with improvements according to the suggestions.